Ageing and growth in the small open economy - Ben J. Heijdra; Ward E. Romp (Center for Economic Studies and ifo Institute (CESifo), 2006)
We construct an overlapping generations model for the small open economy which incorporates a realistic description of the mortality process. Agents engage in educational activities at the start of life and thus create human capital to be used later on in life for production purposes. Depending on the strength of the intergenerational externality in the human capital production function, the model gives rise to exogenous or endogenous growth. The effects of demographic shocks and fiscal stimuli on the growth path are derived, both at impact, during transition, and in the long run.
Keywords: E10; D91; O40; F41; J11; 330